Influence of Weight on Shared Core Symptoms in Eating Disorders: Support or Challenge for a Transdiagnostic Perspective?. (September 2016) - Schmitz, Catalina; Schnicker, Katja; Legenbauer, Tanja
In terms of the transdiagnostic model of eating disorders, Anorexia Nervosa (AN), Bulimia Nervosa (BN), and Binge Eating Disorder (BED) share the same distinctive psychopathology. However, empirical evidence showing similarities between these eating disorder diagnoses for core symptoms is scarce, and the role of weight status is unclear. Data from a total of 168 female participants were collected between April 2004 and April 2008, at an outpatient unit specialized in eating disorder treatment. Core symptoms of eating disorders were measured via self-report questionnaires. In particular, women with BED and BN showed similar patterns of core symptomatology compared with AN. However, when body mass index (BMI) was considered in the analyses, there were no differences between the three diagnostic groups in relation to body image. Differences in eating behavior are not solely triggered by weight differences, whereas body image disturbances are a transdiagnostic phenomenon among EDs and should also be considered in the treatment of BED.